The truck trailer suspension axles failure analysis and modelling - Tretjakovas, Jurijus; Čereška, Audrius (Transport, 2021)
The purpose of trucks is very diverse, but the main purpose is freight transportation. When cargos are transported, the truck’s suspensions are heavily loaded, so failures also occur most often in the suspension elements. For axles of trailers – tubular construction failures occur, they crack. Axle failure investigations are required to determine the cause of the failure. The paper analyses three-axle truck trailer suspension. Axle failure analysis and axial deformation modelling were performed to determine trends and causes of truck trailer suspension axle failures. Different cases with axles of tubular construction with wall thicknesses of 9 and 11 mm were modelled. The paper presented visual failure analysis of truck trailers suspension axles and finite element modelling results of axle’s deformation of different geometrical parameters. The results were discussed and conclusions were drawn. First published online 21 May 2021